Perceived overall service quality and customer satisfaction: A comparative analysis between local and foreign banks in Malaysia - Moghavvemi, Sedigheh; Lee, Su Teng; Lee, Siew Peng (Emerald, 2018)
Purpose: Foreign and local banks in Malaysia are competing in terms of skilled staff, innovative products and services, rendering quality services and customer satisfaction. The purpose of this paper is to examine the overall service quality and customer satisfaction of both foreign and local banks. Design/methodology/approach: The data used to test the hypothesis were collected from 748 foreign and local bank customers in Malaysia. The research model was analysed using a structural equation modelling technique. Findings: Results show that knowledge and staff competencies, as well as convenience of the bank is more significant for local bank customers while bank image and internet banking are important components for foreign bank customers. The results also reveal that foreign bank customers have higher satisfaction as compared to local bank customers. Research limitations/implications: No analysis is undertaken of any difference in the service quality dimensions between banks of different size. Further research on banking services could usefully test services quality dimensions across banks of different sizes. Practical implications: The findings serve as a valuable reference for local banks understand service quality challenges they may face from foreign banks in this competitive industry. Findings suggest that, to provide high-quality services, financial institutions need to heighten customer satisfaction differentiation strategies. Originality/value: The outcomes of this study enhance the knowledge on the performance of both local and foreign banks in Malaysia as well as customer satisfaction, which are invaluable to all bank managers and industry players in improving their services.